DevOps for serverless applications : design, deploy, and monitor your serverless applications using DevOps practices - Bangera, Shashikant (Packt Publishing, 2018)
Set up complete CI and CD pipelines for your serverless applications using DevOps principles Key Features Understand various services for designing serverless architecture Build CD pipelines using various cloud providers for your serverless applications Implement DevOps best practices when building serverless applications Book Description Serverless applications are becoming very popular among developers and are generating a buzz in the tech market. Many organizations struggle with the effective implementation of DevOps with serverless applications. DevOps for Serverless Applications takes you through different DevOps-related scenarios to give you a solid foundation in serverless deployment. You will start by understanding the concepts of serverless architecture and development, and why they are important. Then, you will get to grips with the DevOps ideology and gain an understanding of how it fits into the Serverless Framework. You'll cover deployment framework building and deployment with CI and CD pipelines for serverless applications. You will also explore log management and issue reporting in the serverless environment. In the concluding chapters, you will learn important security tips and best practices for secure pipeline management. By the end of this book, you will be in a position to effectively build a complete CI and CD delivery pipeline with log management for serverless applications. What you will learn Explore serverless fundamentals and effectively combine them with DevOps Set up CI and CD with AWS Lambda and other popular Serverless service providers with the help of the Serverless Framework Perform monitoring and logging with serverless applications Set up a dynamic dashboard for different service providers Discover best practices for applying DevOps to serverless architecture Understand use cases for different serverless architectures Who this book is for DevOps for Serverless Applications is for DevOps engineers, architects, or anyone interested in understanding the DevOps ideology in the serverless world. You will learn to use DevOps with serverless and apply continuous integration, continuous delivery, testing, logging, and monitoring with serverless.